2018
DOI: 10.1097/iae.0000000000001809
|View full text |Cite
|
Sign up to set email alerts
|

Contamination of Anti-Vegf Drugs for Intravitreal Injection

Abstract: All three tested agents are available in similar quality regarding particulate purity and silicone oil microdroplet count. Repackaging can have a major impact on the quality.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
6
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 26 publications
(7 citation statements)
references
References 37 publications
1
6
0
Order By: Relevance
“…The IVT studies are routinely conducted in the cynomolgus monkey and accepted by regulatory agencies because the anatomy of the monkey eye is very similar to that of the human eye. The location of the silicone oil droplets at the dosing site and appearance as multifocal clear spheres or smaller fine white vitreous floaters is consistent with silicone droplets reported in the human clinical studies 4,5,7,13,14 indicating that this preclinical finding translates from cynomolgus monkeys to humans and that the monkey model can be used to further investigate this phenomenon. Investigation into previous preclinical studies revealed 2 studies conducted in dog and 1 in rabbit that did not support our hypothesis that this phenomenon would translate for all species.…”
Section: Discussionsupporting
confidence: 82%
See 2 more Smart Citations
“…The IVT studies are routinely conducted in the cynomolgus monkey and accepted by regulatory agencies because the anatomy of the monkey eye is very similar to that of the human eye. The location of the silicone oil droplets at the dosing site and appearance as multifocal clear spheres or smaller fine white vitreous floaters is consistent with silicone droplets reported in the human clinical studies 4,5,7,13,14 indicating that this preclinical finding translates from cynomolgus monkeys to humans and that the monkey model can be used to further investigate this phenomenon. Investigation into previous preclinical studies revealed 2 studies conducted in dog and 1 in rabbit that did not support our hypothesis that this phenomenon would translate for all species.…”
Section: Discussionsupporting
confidence: 82%
“…These structures had thicker walls and, as in the 14-week study, appeared identical to those described as silicone oil droplets in humans dosed with a variety of biologics in a clinical setting. 4,5,7,13,14 The affected animals in the historical studies also exhibited no appreciable impact on vision associated with the floaters/spheres (although our abilities to detect such changes in animals is limited), and there was also no evidence that the material was associated with a greater inflammatory response or alteration in intraocular pressure.…”
Section: Resultsmentioning
confidence: 97%
See 1 more Smart Citation
“…For instance, if the silicone oil lubrication were similar in two syringe types, fewer oil droplets would be expected in the syringe in the syringe with more dead space. Schargus et al [16]. conducted steady-state biophysical analyses that showed that original prefilled ranibizumab (Lucentis, Genentech, Inc., South San Francisco, CA) glass syringes, original vials with aflibercept, and repacked ready-to-use plastic syringes filled with bevacizumab (Avastin, Genentech, Inc.) from a compounding pharmacy are similar regarding particulate purity and silicone oil microdroplet counts.…”
Section: Discussionmentioning
confidence: 99%
“…Manufacturing processes (e.g., fermentation, purification, formulation, filling, shipment and storage) of biopharmaceuticals can also lead to aggregation, especially upstream prior to formulation [ 28 ]. Aggregation can occur due to shear and filling steps, multiple freeze–thaw cycles, compounding and mechanical shock [ 29 , 30 ]. Aggregation also presents significant challenges in manufacturing due to reduction in yields [ 31 ].…”
Section: General Challenges In Polypeptide Deliverymentioning
confidence: 99%